2011
DOI: 10.1002/bit.23184
|View full text |Cite
|
Sign up to set email alerts
|

A new direction for anticoagulants: Inhibiting fibrin assembly with PEGylated fibrin knob mimics

Abstract: Current anticoagulants target coagulation Factors upstream from fibrin assembly and polymerization (i.e. formation of fibrin clot). While effective, this approach requires constant patient monitoring since pharmacokinetics and pharmacodynamics vary from patient to patient. To address these limitations, we developed an alternative anticoagulant that effectively inhibits fibrin polymerization. Specifically, we investigated PEGylated fibrin knob `A' peptides, evaluating the effect of both PEG chain length (0, 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Regardless, the differences between these findings demonstrate fundamental differences in the hypercoagulable mechanisms of elevated fibrinogen and elevated FVIII, and they suggest antithrombotic strategies could be tailored for a specific hypercoagulability (blocking thrombin generation/activity vs blocking fibrin formation). 46 Our findings on the relationship between vascular injury and effect of FVIII on thrombosis inform epidemiologic studies showing either moderate or no relationship between FVIII and arterial thrombosis. 9,10,12,13 Using the presence of carotid plaque as a marker of mild or moderate disease, Pan et al showed a significant association between heart disease and FVIII level (OR ϭ 2.65).…”
Section: Elevated Fviii and Vascular Injury In Thrombosismentioning
confidence: 66%
See 1 more Smart Citation
“…Regardless, the differences between these findings demonstrate fundamental differences in the hypercoagulable mechanisms of elevated fibrinogen and elevated FVIII, and they suggest antithrombotic strategies could be tailored for a specific hypercoagulability (blocking thrombin generation/activity vs blocking fibrin formation). 46 Our findings on the relationship between vascular injury and effect of FVIII on thrombosis inform epidemiologic studies showing either moderate or no relationship between FVIII and arterial thrombosis. 9,10,12,13 Using the presence of carotid plaque as a marker of mild or moderate disease, Pan et al showed a significant association between heart disease and FVIII level (OR ϭ 2.65).…”
Section: Elevated Fviii and Vascular Injury In Thrombosismentioning
confidence: 66%
“…Regardless, the differences between these findings demonstrate fundamental differences in the hypercoagulable mechanisms of elevated fibrinogen and elevated FVIII, and they suggest antithrombotic strategies could be tailored for a specific hypercoagulability (blocking thrombin generation/activity vs blocking fibrin formation). 46 …”
mentioning
confidence: 99%
“…PL and fibrin hydrogels were formed as described above at a volume of 0.5 mL and polymerized in 24-well 1.5 glass bottom tissue culture plates[20,21]. Laser scanning confocal microscopy (LSM 700, Carl Zeiss, Inc.) with a 63X oil immersion objective was performed for visualization of the fibrin network using 5% FITC-labeled fibrinogen (Sigma).…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…These mimics can then be used alone, or in conjunction with carrier materials, to modify fibrin structure. We subsequently created a variety of knob mimic constructs including knob A -protein constructs, PEGylated knobs A and B and knob A modified elastin-like peptide (ELP) micelles and characterized their effect on fibrin properties such as polymerization, degradation and mechanical properties and network structure [31, 43, 151153]. Knob A -protein constructs designed to display the tetrapeptide sequences GPRP, GPRV, GHRP or GSPE (non-binding control) at the N-termini of a protein fragment, specifically the cell binding 9th and 10th type III repeats of fibronectin, were found to stably bind fibrinogen via specific knob:hole interactions and were retained within fibrin matrices for 24 hours, therefore showing promise as a potential method for drug release from fibrin matrices [152].…”
Section: Modulation Of Fibrin Propertiesmentioning
confidence: 99%
“…These perturbations were not observed in matrices formed in the presence of 7.5 kDa GPRP2 -PEG, 10 kDa and 20 kDa GPRP4 -PEG (Figure 5L, P, R). In additional studies, our group has created PEG- knob constructs with higher affinity for fibrinogen through conjugation of a linear 5 kDa PEG to the GPRPFPAC sequence; addition of this construct to fibrin matrices was found to increase network porosity compared to the peptide sequence alone [151]. Likewise, studies utilizing a PEGylated knob B mimic, AHRPYAAC, found that this construct also enhanced the porosity of the fibrin network (Figure 6) and increased susceptibility to degradation, though interestingly, these constructs resulted in an increase in the complex modulus [43].…”
Section: Modulation Of Fibrin Propertiesmentioning
confidence: 99%